Evaluation of antimicrobial properties of nano-silver particles used in orthodontics fixed retainer composites: an experimental in-vitro study - Amirhossein Mirhashemi; Abbas Bahador; Ahmad Sodagar; Maryam Pourhajibagher; Ali Amiri; Elahe Gholamrezayi (Tabriz University of Medical Sciences, 2021)
Background. The present study evaluated the antimicrobial efficacy of composite resins containing nano-silver (NAg) particles used in fixed orthodontic retainers. Methods. Nano-composite resin samples with 1%, 2%, and 5% concentrations of NAg were prepared. The antimicrobial effectiveness of NAg was assessed against Streptococcus mutans, Streptococcus sanguis, and Lactobacillus acidophilus by the biofilm inhibition test (three-day-old biofilms), eluted components test (on days 3, 15, and 30), and disk-diffusion agar test after 48 hours. Measures of central tendency and index of dispersion were used to determine colony-forming units. Kruskal-Wallis test and Mann-Whitney U test were also used. Results. The biofilm inhibition test showed a significant decrease in the colonies of S. mutans (87.64%, 96.47%, and 99.76% decrease), S. sanguis (98.13%, 99.47%, and 99.93% decrease), and L. acidophilus (81.59%, 90.90%, and 99.61% decrease) at 1%, 2%, and 5% concentrations of Nag, respectively, compared to the control groups. The colony-forming unit (CFU)/mL of tested microorganisms continuously decreased with increased NAg concentration. In the eluted component test, no significant differences were noted in the 3rd, 15th, and 30th days between the different concentrations of Nag-containing composite resin disks and control samples. According to the disk-diffusion agar test, there was no growth inhibition zone for the composite resin disks containing 1% and 2% concentrations of Nag. However, the growth inhibition zone was seen with a 5% concentration, with a diameter of 9.5±0.71 mm for S. mutans, 8.5±0.71 mm for S. sanguis, and 8±1.41 for L. acidophilus. Conclusion. The incorporation of NAg into composite resins has antibacterial effects, possibly preventing dental caries around fixed orthodontic retainers.